The Influence of Foreign Direct Investment, Government Expenditure, Trade, and Inflation on Economic Growth in Indonesia - Rahmawati, Umiati Nur; Dewi, Dita Dismalasari (Journal of Tourism Economics and Policy, 2026)
This study aims to examine the influence of Foreign Direct Investment (FDI), Government Expenditure, Economic Openness, and Inflation on Indonesia’s economic growth during the 1994–2024 period. The research applies a quantitative descriptive approach using annual secondary data obtained from the World Bank’s World Development Indicators and employs multiple linear regression analysis with the Ordinary Least Squares method. The analysis reveals that the four macroeconomic variables collectively have a significant effect on Indonesia’s economic growth, demonstrating that the selected model is appropriate to explain changes in the country’s economic performance. The findings show that FDI plays a vital role as a key driver of growth by enhancing capital accumulation, technology transfer, employment creation, and industrial capacity. Government expenditure shows a negative but insignificant influence, indicating that ineffective or consumption-oriented spending limits its contribution to economic development. Economic openness has a significant negative impact, suggesting that Indonesia’s trade structure during the study period was dominated by imports, which hindered domestic production and long-term growth. Inflation exhibits a positive but insignificant effect, reflecting a stable inflationary environment that neither promoted nor constrained economic expansion. This study concludes that increasing productive FDI inflows, improving the efficiency and allocation of government spending, fostering export-oriented trade policies, and maintaining stable inflation are crucial strategies to achieve sustainable and inclusive economic growth in Indonesia.